Taxation and State during the Greek Revolution: Comments on the Tax Registers (1822 and 1829) - Sarafis, Vangelis (The Historical Review/La Revue Historique, 2025)
This article investigates the fiscal mechanisms of the Greek state during the Greek Revolution, with a particular focus on taxation and the institutional formation of the public finances between 1822 and 1829. Drawing on underexplored fiscal documents – such as tax registers and auction records – it examines how the Provisional Administration sought to establish a centralised revenue system through the abolition of Ottoman personal taxes, the introduction of tithe-based taxation and the leasing of public revenues. The analysis highlights both continuities with Ottoman fiscal practices and significant innovations aimed at legitimising and consolidating state authority under revolutionary conditions.